Overview of Religiosity of Intensive Care Unit Nurses: A Narrative Review - Irfandi Rahman; Anastasia Anna; Aan Nuraeni (GLOBAL HEALTH SCIENCE GROUP, 2024)
The high demands on intensive care unit (ICU) nurses can be a source of stressors and cause distress for nurses. When nurses lack effective coping skills to deal with problems in the workplace, this can add to the stress levels of ICU nurses. Nurses' religiosity can affect nurses' beliefs in carrying out their duties as ICU nurses. The purpose of this narrative review was to understand and describe the religiosity of nurses in the intensive care unit. The method used was a narrative review with researchers searching for articles from quantitative and qualitative studies collected from electronic databases such as Pubmed, EBSCO, Cinahl, Science Direct, and Google Scholar, with keywords: religiosity, nurse, intensive care unit. We found ten articles and identified four themes related to the topic, namely: 1) the impact of nurses' religiosity, 2) dimensions of nurses' religiosity, 3) factors affecting nurses' religiosity, and 4) instruments to measure religiosity, namely: CRS, DSES, SSCRS, DUREL, PFS, PEMS, DRIS-F, MQS-T, and NSCTS.